Exposure to Reproductive Health Information and Behavior in Islamic Boarding School, Sinjai District - Luqman, Naurah Khalilah; Raodhah, Sitti; Wijaya, Dian Rezki (Diversity: Disease Preventive of Research Integrity, 2023)
Improving reproductive health for adolescents is one of the efforts to improve the quality of human life which will increase the human resource index in the future. This study aims to determine the effect of information exposure on adolescent reproductive health behavior. This study used a quantitative research method with a cross sectional approach to female students at the Darul Ihsan Islamic Boarding School, East Sinjai District, Sinjai Regency with a total of 68 respondents. The results showed that the information exposure variable had a relationship with attitude (p=0.006) then what was not related was the knowledge level variable (p=0.121) and the action variable (p=0.091). The results of the multivariate analysis showed that information exposure had an influence on attitudes with a 5.857 chance of reproductive health behavior for young female students at Islamic boarding schools. This study provides information to young female students to be tabayun to all health information obtained and to increase their knowledge regarding reproductive health. Good health information in terms of maintaining cleanliness will be a very important asset during adolescence.